DETERMINATION OF 2,4-DICHLOROPHENOXYACETIC ACID (2,4-D) FROM TOMATOES BY LC-MS/MS ANALYSIS - COSTEA, Liana Maria; RAD, Raluca; CIMPOIU, Claudia; MEGHESAN, Adela (Studia Universitatis Babeș-Bolyai Chemia, 2022)
2,4-D is a herbicide that in certain doses can be used as a growth stimulator for various crops. Although it is forbidden in our country to use it for such purposes, tomato growers use it to obtain large and fast harvests, but unfortunately of poor quality (the well-known tomatoes with tassel). In this work, we present a modified Miniluke extraction method and a LC-MS/MS analysis method of this pesticide from tomatoes. The method was validated both on tomatoes (presented in this paper) and strawberries, and its efficiency was demonstrated by participating to interlaboratory European tests where very good Z-scores were obtained.